2015
DOI: 10.1097/gme.0000000000000399
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and cardiovascular disease in postmenopausal women

Abstract: Well-designed research, with CVD as primary outcome, is needed to help bridge the gap in our knowledge on this topic. In the meantime, caution should be applied to avoid overdiagnosis and overtreatment of vitamin D deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Menopause may be considered a risk factor for VDD and, consequently, secondary hyperparathyroidism (25,36). It is also known that cardiovascular risk increases in menopause with hormonal changes (26,36). In postmenopausal women, Pirro M. et al showed that VitD insu ciency was associated with arterial stiffness weakly.…”
Section: Discussionmentioning
confidence: 99%
“…Menopause may be considered a risk factor for VDD and, consequently, secondary hyperparathyroidism (25,36). It is also known that cardiovascular risk increases in menopause with hormonal changes (26,36). In postmenopausal women, Pirro M. et al showed that VitD insu ciency was associated with arterial stiffness weakly.…”
Section: Discussionmentioning
confidence: 99%
“…While there are data to suggest calcium + Vitamin D has some beneficial effects on cardiovascular disease risk factors 11,14,15 , this has not been well-established, and there is a paucity of prospective data regarding the effect of calcium + Vitamin D on cardiovascular disease outcomes 16,17 . More recent data have suggested that estrogen therapy alone, in younger women closer to the time of menopause (the timing hypothesis) could have beneficial cardiovascular disease outcomes, particularly lower rates of myocardial infarction 12,18-21 , but no significant reduction was observed with younger women randomized to estrogen plus progestogen therapy 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In skin 7-dehydrocholesterol can be converted to previtamin D 3 after absorbing solar ultraviolet B radiation and then sequentially hydroxylated into 25(OH)D and 1,25-dihydroxyvitamin D 3 (an active form) by hydroxylases in the liver and kidney. Vitamin D can be also ingested in the diet or by oral supplements [ 1 ]. Besides its classical physiological function of regulation of calcium and bone metabolism, vitamin D is suggested to have many other functions such as modulating immune function, anti-inflammatory activity, suppressing the rennin-angiotensin system and reducing insulin resistance [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%